Synthesis of multimodal porous ZnCo2O4 and its electrochemical properties as an anode material for lithium ion batteries - Hao, Shiji; Zhang, Bowei; Ball, Sarah; Copley, Mark; Xu, Zhichuan; Srinivasan, Madhavi; Zhou, Kun; Mhaisalkar, Subodh; Huang, Yizhong (Journal of power sources, 2015)
In the present paper, flower-like multimodal porous ZnCo2O4 microspheres, comprised of numerous nanosheets, are synthesized through PVP assist solvothermal self-assembling process. The multimodal porous ZnCo2O4 microspheres are characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). A possible formation mechanism of two steps self-assemble is proposed. The ZnCo2O4 microspheres are then used as an anode material to fabricate lithium ion batteries. The results based on the evaluation of lithium ion batteries demonstrate that the porous microstructure offers the excellent electrochemical performance with high capacity and long-life cycling stability. It is found that a high reversible capacity of 940 and 919 mAh g−1 is maintained after 100 cycles at a low charge–discharge rate of 0.1C and 0.2C (100 and 200 mA g−1), respectively. Meanwhile, the remaining discharging capacity reaches as high as 856 mAh g−1 after 1000 cycles subject to the large current density up to 1C. •ZnCo2O4 multimodal porous microspheres are prepared via solvothermal method.•Two-step formation mechanism of flower like precursor is proposed.•ZnCo2O4 delivers high rate capability and long lifespan.